PENINGKATAN KINERJA RUAS JALAN DENGAN PENGURANGAN HAMBATAN SAMPING PADA RUAS JALAN GAJAH MADA MEULABOH KAB. ACEH BARAT - Faisal Arif; Muhammad Isya; Renni Anggraini (Prodi Magister Teknik Sipil Unsyiah, 2020)
Gajah Mada street is the main street of Meulaboh City, which serves traffic from or to Banda Aceh City. In the Gajah Mada street area, there are offices, educational facilities and public hospital facilities, and there are also trade centers such as supermarkets, restaurants and coffee shops. This emerges an impact in the form of decreasing the level of service (LOS) on the street, because it triggers side barriers. This study aims to determine the level of service on the Gajah Mada street section and provide an alternative treatment in maintaining the level of street service on these streets. From the processing of data obtained the results of degree of saturation (DS) for three days of observation for each direction of the Gajah Mada street. In the direction of the Kisran intersection – Rudeng intersection, DS on Monday at 0,47, DS on Thursday at 0,55 and DS on Saturday at 0,48. As for the direction of the Rundeng intersection – Kisaran intersection, DS on Monday is 0.44, DS on Thursday is 0,49 and DS on Saturday is 0,45. From the results of data analysis, the level of service obtained in both directions of Gajah Mada is on LOS C. Thus the performance of the Gajah Mada street still qualifies for urban streets. Alternative handling to increase LOS on Gajah Mada street can be done with a side obstacle reduction scenario, with this scenario it can reduce the degree of saturation from 0,55 in the existing condition to 0,27 under conditions after handling. So that in this condition the service level of Gajah Mada is on LOS A